Commuting and self-employment in Western Europe - José Ignacio Giménez-Nadal; José Alberto Molina; Jorge Velilla (Global Labor Organization (GLO), 2020)
This paper explores the commuting behavior of workers in Western European countries, with a focus on the differences in commuting time between employees and the self-employed in these countries. Using data from the last wave of the European Working Conditions Survey (2015), we analyze the commuting behavior of workers, finding that male and female self-employed workers devote 14% and 20% less time to commuting than their employee counterparts, respectively. Furthermore, differences in commuting time between employees and self-employed females depend on the degree of urbanization of the worker's residential location, as the difference in commuting time between the two groups of female workers is greater in rural areas, in comparison to workers living in urban areas. By analyzing differences in commuting time between groups of European workers, our analysis may serve to guide future planning programs.
Keywords: R40; O57; 330; Commuting time; European Working Conditions Survey; Self-employed workers; Employees